Deviations from Politeness Principles in Humor Content on The YouTube Account @Tretan Universe - Ramadhani, Fatimah Nurul; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to describe and analyze the forms of politeness principle deviations in humorous content on the @Tretan Universe YouTube account. The phenomenon warrants investigation as it involves intricate communication strategies that balance humor creation with linguistic propriety. Employing a qualitative descriptive approach, this research analyzes utterances from the 22-minute podcast "Reveal Mutants 'SUGENG TUMBLER' ft. Obing." Data collection employed non-participant observation and note-taking techniques, with analysis conducted using the distributional method and validated through theoretical triangulation. Findings identify five violation types: (1) tact maxim violations (3 instances) through unfavorable comparisons, direct criticism, and repetitive queries; (2) generosity maxim violation (1 instance) via self-benefit maximization; (3) approbation maxim violations (3 instances) through disparagement, inappropriate analogies, and interlocutor belittlement; (4) agreement maxim violations (2 instances) via uncooperative responses and repetitive questioning; and (5) sympathy maxim violation (1 instance) through antipathy maximization. These violations demonstrate that politeness breaches in humorous content constitute not merely instances of impoliteness but rather deliberate communicative strategies employed to establish rapport with the audience.